PENGARUH PENDEKATAN KONTEKSTUAL BERBANTUAN MEDIA GEOGEBRA TERHADAP KEMAMPUAN PEMAHAMAN DAN DISPOSISI MATEMATIS SISWA - Mulyati, Ai Sri; Sudin, Ali; Irawati, Riana (Jurnal Pena Ilmiah, 2019)
The research aimed to determine the improvement of students 'mathematical understanding and disposition on the Contextual Approach assisted by Geogebra media and conventional learning models, to find out the differences between the use of the Contextual Approach assisted by Geogebra media and conventional learning model sons tudents' mathematica understanding and disposition ability mathematical understanding and disposition. The research method used is quasi-experimental design with nonequivalent control group design. The subjects in this study were fourth grade students of SDN Cikawung I (experiment) and SDN Cikawung III (control). The results obtained are: 1) Contextual Approach assisted by Geogebra media and conventional learning models improve the ability of understanding and mathematical disposition significantly, 2) Contextual approach assisted by Geogebra media and conventional learning models can significantly improve mathematical dispositions, 3) to positive relationships between abilities mathematical understanding and disposition, 4) students respond well to learning activities.